Perencanaan Manajemen Strategi Dalam Membangun UMKM Menurut Pandangan Islam - Indah Pratiwi; Chuzaimah Batubara (LPPM Universitas Labuhanbatu, 2025)
SMEs often face limited resources, including capital, labor, and access to information. These limitations can affect the ability of MSMEs to conduct in-depth market analysis, develop long-term strategies, and implement necessary changes. Effective strategic management can assist MSMEs in achieving market differentiation, exploiting local advantages, and optimizing limited resources. MSMEs can also take advantage of their speed and flexibility to respond quickly to market changes, utilize information and communication technology to improve operational efficiency, and build strong relationships with customers and business partners. In addition, MSMEs also need to improve their ability to manage risk, develop strategic partnerships, and improve the quality of their products or services. In conclusion, strategic management is an important element in the success of SMEs. Although MSMEs face unique challenges, they also have opportunities to achieve competitive advantage through effective strategic management. By adopting the right approach and utilizing available resources, MSMEs can face competition successfully, optimize business growth, and make a positive contribution to the local and regional economy.